2004
DOI: 10.1007/s00425-004-1206-9
|View full text |Cite
|
Sign up to set email alerts
|

Seed-specific transcription factors ABI3 and FUS3: molecular interaction with DNA

Abstract: In Arabidopsis thaliana (L.) Heynh. the seed-specific transcription factors ABI3 and FUS3 have key regulatory functions during the development of mature seeds. The highly conserved RY motif [DNA motif CATGCA(TG)], present in many seed-specific promoters, is an essential target of both regulators. Here we show that, in vitro, the full-length ABI3 protein, as well as FUS3 protein, is able to bind to RY-DNA and that the B3 domains of both transcription factors are necessary and sufficient for the specific interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 39 publications
8
141
1
1
Order By: Relevance
“…Recent studies have demonstrated that they directly controlled the induction of SSP gene expression, recognizing the RY motifs present in the promoters of these target genes Reidt et al, 2000;Kroj et al, 2003;Mö nke et al, 2004;Braybrook et al, 2006). Accordingly, we found that FUS3 is able to specifically bind the RY element of the SDH2-3 promoter in EMSA assays (Fig.…”
Section: B3 Domain Transcription Factors Regulate Sdh2-3supporting
confidence: 58%
See 2 more Smart Citations
“…Recent studies have demonstrated that they directly controlled the induction of SSP gene expression, recognizing the RY motifs present in the promoters of these target genes Reidt et al, 2000;Kroj et al, 2003;Mö nke et al, 2004;Braybrook et al, 2006). Accordingly, we found that FUS3 is able to specifically bind the RY element of the SDH2-3 promoter in EMSA assays (Fig.…”
Section: B3 Domain Transcription Factors Regulate Sdh2-3supporting
confidence: 58%
“…FUS3 and ABI3 Bind the SDH2-3 Promoter RY motifs are putative targets for B3 domain transcription factors (Suzuki et al, 1997;Reidt et al, 2000;Kroj et al, 2003;Mö nke et al, 2004). To investigate whether these factors could recognize in vitro the SDH2-3 RY promoter element, ABI3 and FUS3 proteins expressed in Escherichia coli were tested for their ability to bind to an oligonucleotide containing this element in an electrophoretic mobility shift assay (EMSA).…”
Section: Abre and Ry Elements Are Required For Sdh2-3 Promoter Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…We found that six copies of the highly conserved RY motif CATGCA(TG), an essential target of FUS3 and ABI3 transcription factors (Mö nke et al, 2004), are present in the AtMYB44 promoter. ABI3 and FUS3 transcription factors are associated with ABA action (Nambara et al, 2000;Gazzarrini et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…The B3 domains of ABI3, FUS3, and LEC2 exhibit binding to sequences containing the RY motif [CATGCA] (Suzuki et al, 1997;Kroj et al, 2003;Mö nke et al, 2004). It is not known at present whether the B3 domains of the HSI2 subfamily proteins exhibit binding to sequences similar to the RY motif.…”
Section: Discussionmentioning
confidence: 99%